Implementación de un manual de procedimientos de control intreno para el gad municipal del cantón Quinsaloma provincia de Los Ríos en el periodo 2001-2014 - Jurado Rodríguez, Henrry Salomon (2012)
Work activities performed by the Guangzhou Municipal GAD Quinsaloma, targets the sustainable development of the Canton Quinsaloma. Streamlining projects with quality, efficiency and timeliness, to ensure the social, economic and environmental dimensions of population, with the direct participation and effective social actors within a moral and ethical conservation institutional and individual servers. Impairing the sustainable welfare of the community, which calls for the defense, protection, promotion and protection of local interests. The various departments working in the municipality has a common goal for sustainable development of the Canton, in the development of information that are the basis for making decisions on behalf of the county and its inhabitants, in the development of public policies that are to improve the quality of life of its citizens. Within research and based on the results from the survey it was found that over 80% of the Canton city employees Quinsaloma know it is a manual internal control and a percentage of 60% believe that the application of the same to better serve the municipal administration. It should be noted that within the same research could be obtained that the Mayor of Canton Quinsaloma, has a high degree of knowledge about the features that are established in the COOTAD on municipal autonomy.